The feasibility and impact of a yoga pilot programme on the quality-of-life of adults with acquired brain injury. (28th January 2017) - Donnelly, Kyla Z.; Linnea, Kate; Grant, Daya Alexander; Lichtenstein, Jonathan
ABSTRACT: Objective : This pilot study measured the feasibility and impact of an 8-week yoga programme on the quality-of-life of adults with acquired brain injury (ABI). Methods : Thirty-one adults with ABI were allocated to yoga ( n = 16) or control ( n = 15) groups. Participants completed the Quality of Life After Brain Injury (QOLIBRI) measure pre- and post-intervention; individuals in the yoga group also rated programme satisfaction. Mann-Whitney/Wilcoxon and the Wilcoxon Signed Rank tests were used to evaluate between- and within-group differences for the total and sub-scale QOLIBRI scores, respectively. Results : No significant differences emerged between groups on the QOLIBRI pre- or post-intervention. However, there were significant improvements on overall quality-of-life and on Emotions and Feeling sub-scales for the intervention group only. The overall QOLIBRI score improved from 1.93 (SD = 0.27) to 2.15 (SD = 0.34, p = 0.01). The mean Emotions sub-scale increased from 1.69 (SD = 0.40) to 2.01 (SD = 0.52, p = 0.01), and the mean Feeling sub-scale from 2.1 (SD = 0.34) to 2.42 (SD = 0.39, p = 0.01). Conclusion : Adults with ABI experienced improvements in overall quality-of-life following an 8-week yoga programme. Specific improvements in self-perception and negative emotions also emerged. High attendance and satisfaction ratings support the feasibility of this type of intervention for people with brain injury.